Regulatory aspects of optogenetic research and therapy for retinitis pigmentosa under EU law - Johannes Freise (Frontiers in Medical Technology)
Optogenetics has potentials for a treatment of retinitis pigmentosa and other rare degenerative retinal diseases. The technology allows controlling cell activity through combining genetic engineering and optical stimulation with light. First clinical studies are already being conducted, whereby the vision of participating patients who were blinded by retinitis pigmentosa was partially recovered. In view of the ongoing translational process, this paper examines regulatory aspects of preclinical and clinical research as well as a therapeutic application of optogenetics in ophthalmology. There is no prohibition or specific regulation of optogenetic methods in the European Union. Regarding preclinical research, legal issues related to animal research and stem cell research have importance. In clinical research and therapeutic applications, aspects of subjects' and patients' autonomy are relevant. Because at EU level, so far, no specific regulation exists for clinical studies in which a medicinal product and a medical device are evaluated simultaneously (combined studies) the requirements for clinical trials with medicinal products as well as those for clinical investigations on medical devices apply. This raises unresolved legal issues and is the case for optogenetic clinical studies, when for the gene transfer a viral vector classified as gene therapy medicinal product (GTMP) and for the light stimulation a device qualified as medical device are tested simultaneously. Medicinal products for optogenetic therapies of retinitis pigmentosa fulfill requirements for designation as orphan medicinal product, which goes along with regulatory and financial incentives. However, equivalent regulation does not exist for medical devices for rare diseases.